Correlation Between Tenofovir Drug Levels and the Renal Biomarkers RBP-4 and ß2M in the ION-4 Study Cohort. (24th January 2019) - Chan, Austin; Park, Lawrence; Collins, Lauren F; Cooper, Curtis; Saag, Michael; Dieterich, Douglas; Sulkowski, Mark; Naggie, Susanna
Abstract: Background: Concomitant dosing of ledipasvir (LDV) and tenofovir disoproxil fumarate (TDF) results in an increased tenofovir (TFV) area under the curve (AUC). The aim of this study was to examine whether there was a correlation between the renal biomarkers retinol binding protein–4 (RBP-4) and β2 microglobulin (β2M) and tenofovir AUC. Methods: The ION-4 trial enrolled HIV/hepatitis C virus–coinfected patients on nonpharmacologically boosted antiretroviral regimens with TDF-containing backbones. We assessed for a correlation between tenofovir AUC and urinary biomarkers and also for changes in serologic biomarkers with respect to clinically relevant changes in renal function (creatinine clearance decrease >25%, change in creatinine >0.2 mg/dL, change in proteinuria from negative/trace to ≥1+). Results: Three hundred thirty-five patients were enrolled in the ION-4 study; their demographic characteristics have been previously described. Both RBP-4 and β2M exhibited positive correlations with tenofovir AUC. Baseline and study levels of RBP-4 and β2M were higher for patients with increases in urine proteinuria and an absolute creatinine increase. Conclusions: TFV exposure is associated with increased proximal tubule urine biomarkers in participants on ledipasvir/sofosbuvir and nonpharmacologically boosted TDF-based antiretroviral regimens. Baseline proximal tubule biomarkers may predict nephrotoxicity risk if events are prevalent. Further studies assessing the predictive role of these urine biomarkers may help guide medical decision-making and risk/benefit assessments in patients with risk factors for renal dysfunction.